A Rare Case of the Digenic Inheritance of Long QT Syndrome Type 2 and Type 6. (20th June 2019) - Heida, Annejet; van der Does, Lisette J. M. E.; Ragab, Ahmed A. Y.; de Groot, Natasja M. S.
Abstract : We report a 37-year-old woman with an out-of-hospital cardiac arrest caused by ventricular fibrillation due to digenic inheritance of long QT syndrome type 2 ( KCNH2 gene) and type 6 ( KCNE2 gene). During hospitalization, prolonged QTc intervals and frequent episodes of ventricular tachyarrhythmias manifested. Genetic testing identified a mutation of the KCNH2 gene and an unclassified variant, most likely pathogenic, of the KCNE2 gene. This digenic inheritance is extremely rare.